Synthesis of Cu2ZnSnS4 (CZTS) Semiconductor Thin Film with Variation of Sulfur Solution Concentration - Sugiarti, Sri; Nugraga, Farhan Dandi; Sjahriza, Ahmad (Departemen Kimia, 2026)
The Cu2ZnSnS4 (CZTS) thin film is an alternative semiconductor material as a light absorbing layer in solar cells. The advantages of CZTS as a light absorbing layer are the availability of abundant materials in nature and high absorption coefficient values. The absorbent layer was prepared using the sol-gel and spin coating method on an indium tin oxide (ITO) glass substrate. Films were made with a sol-gel solution with varying concentrations of sulfur solution, namely with a concentration of 3M and 6M using a simple spin coating tool which was rotated for 30 seconds. The film formed was hardened at 550°C for 60 minutes under N2 gas. The results of X-ray diffraction analysis showed that the CZTS thin films formed from the two samples had a kesterite crystal structure with a small percentage. Samples with a sulfur solution concentration of 6M had a higher percentage of crystals with a percentage of 13.26% with a film thickness of 3.73-4.73 μm, while the sulfur solution concentration of 3M has a percentage of 7.54%. The CZTS thin film sample with 6M sulfur concentration has a bandgap energy of 1.88 eV and the absorption coefficient value obtained is 5 x 103cm-1 which is the best result. In conclusion, the spin coating method has the potential to be used to produce kesterite ZCTS under relatively high concentrations of sulfur solution.